Some theoretical questions about the G-particle-hole hypervirial equation - Valdemoro, C. (2011)
By applying a matrix contracting mapping, involving the G-particle-hole operator, to the matrix representation of the N-electron density hypervirial equation, one obtains the G-particle-hole hypervirial (GHV) equation (Alcoba, et al., Int J Quant Chem 2009, 109, 3178). This equation may be solved by exploiting the stationary property of the hypervirials (Hirschfelder, J Chem Phys 1960, 33, 1462; Fernández and Castro, Hypervirial Theorems., Lecture Notes in Chemistry Series 43, 1987) and by following the general lines of Mazziotti's approach for solving the anti-Hermitian contracted Schrödinger equation (Mazziotti, Phys Rev Lett 2006, 97, 143002), which can be identified with the second-order density hypervirial equation. The accuracy of the results obtained with this method when studying the ground-state of a set of atoms and molecules was excellent when compared with the equivalent full configuration interaction (FCI) quantities. Here, we analyze two open questions: under what conditions the solution of the GHV equation corresponds to a Hamiltonian eigenstate, and the possibility of extending the field of application of this methodology to the study of excited and multiconfigurational states. A brief account of the main difficulties that arise when studying this type of states is described. © 2010 Wiley Periodicals, Inc.